Evaluation of OTTV Values for Glass Facades in the Domestic Waiting Area at Sultan Hasanuddin Airport - Deni Priansyah; Desfitriana Jelita Aisyah Zulbahri (Program Studi Arsitektur, Fakultas Teknik, Universitas Katolik Parahyangan, 2026)
This study evaluates the thermal performance of a full-glass facade in a tropical airport terminal building using the Overall Thermal Transfer Value (OTTV) method based on SNI 03-6389-2020. A quantitative, evaluative case study approach was applied to the domestic departure waiting area of Sultan Hasanuddin International Airport, which is characterized by a window-to-wall ratio (WWR) of 1. The results show that the OTTV value reached 87.11 W/m², exceeding the maximum standard of 35 W/m² by 2.49 times. The dominant contribution comes from solar radiation through the glass (57.96 W/m²), followed by conductive heat transfer (29.15 W/m²), while conduction through the opaque walls is negligible due to the full-glass facade configuration. These findings indicate that full-glass facades without adequate thermal control are unsuitable for tropical climates, as they significantly increase cooling loads and energy demand. This study highlights the importance of facade design strategies, such as low-mission glass, external shading, and optimized ratios, to improve building energy performance.